2007
DOI: 10.1111/j.1365-2044.2007.05186.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of albumin 5% and artificial colloids on clot formation in small infants

Abstract: SummaryAlbumin is often cited in textbooks as the gold standard for fluid replacement in paediatrics, but in practice artificial colloids are more frequently used. Although one concern with the use of artificial colloids is their intrinsic action on haemostasis, the available data in children are inconclusive for 6% hydroxyethyl starch 130 ⁄ 0.4 (HES) and no data exist for gelatine solution with respect to coagulation. A total of 42 children (3-15 kg) undergoing surgery and needing colloid replacement were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
33
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 42 publications
8
33
0
2
Order By: Relevance
“…The influence of colloids on hemostasis was investigated in a prospective trial in small children (3-15 kg body weight) who randomly received a bolus of 15 ml/kg of either albumin 5%, 4% modified gelatin solution or 6% hydroxyethyl starch (HES 130/0.4) after induction of anesthesia [38]. Fibrin polymerization as measured with the ROTEM FibTEM test was significantly decreased in all groups, but most pronounced in the HES group.…”
Section: Influence Of Colloids On the Development Of Dilutional Coagumentioning
confidence: 99%
“…The influence of colloids on hemostasis was investigated in a prospective trial in small children (3-15 kg body weight) who randomly received a bolus of 15 ml/kg of either albumin 5%, 4% modified gelatin solution or 6% hydroxyethyl starch (HES 130/0.4) after induction of anesthesia [38]. Fibrin polymerization as measured with the ROTEM FibTEM test was significantly decreased in all groups, but most pronounced in the HES group.…”
Section: Influence Of Colloids On the Development Of Dilutional Coagumentioning
confidence: 99%
“…Die Blutgerinnung wird in erster Linie durch den Verdünnungseffekt sowie durch eine Fibrinpolymerisationsstörung beeinträchtigt. In experimentellen und klinischen Studien war dieser Effekt im Vergleich zu HES geringer ausgeprägt [12,19].…”
Section: Volumenersatzunclassified
“…In healthy volunteers, diluting with various colloidshydroxyethyl starch (HES) [10] or Gelofusine [11]-results in a worsening of the coagulation parameters. Haas et al [12] found that in pediatric surgery, 6% HES 130/0.4 (Voluven Ò ) resulted in the most pronounced increase in clot formation time, reduced clot firmness, slowed clot propagation, and reduced fibrin polymerization compared to the baseline. The effects were less pronounced with 5% albumin and even less for 4% gelatine.…”
Section: Colloidsmentioning
confidence: 99%